Coexistence of Familial Mediterranean Fever With Ankylosing Spondylitis and Sjogren’s Syndrome: A Rare Occurrence - Fulya DÖRTBAŞ; Yeşim GARİP and Tuba GÜLER and Ayşe Aslıhan KARCI (Archives of Rheumatology, 2016)
Familial Mediterranean fever is an autosomal recessive disease characterized by recurrent episodes of fever, peritonitis, synovitis, pleuritis, and erysipelas-like skin lesions. Sjogren’s syndrome is a chronic autoimmune disorder characterized by dry eyes, dry mouth, and musculoskeletal involvement. Ankylosing spondylitis is an autoinflammatory rheumatic disease which affects mainly the axial skeleton. To our knowledge, coexistence of familial Mediterranean fever with ankylosing spondylitis and Sjogren’s syndrome has not been reported previously in the literature. In this article, we report an unusual case of three autoinflammatory diseases in one patient.